Evaluation of non - alcoholic fatty liver disease in hypothyroidism in a tertiary care hospital in southern India - Basavaraj V. Savadi; Lingraj Patil; Poojadevi Malipatil; Shrish Patil (Al Ameen Medical College, 2024)
Background: NAFLD ranges from simple fatty liver to non-alcoholic steatohepatitis, which may progress to liver fibrosis, cirrhosis and hepatocellular carcinoma. Subclinical hypothyroidism is associated with metabolic syndrome, cardiovascular mortality and disturbance of lipid metabolism. Objective: To study the association between NAFLD and hypothyroidism. Methods: A cross-sectional study was conducted at a tertiary hospital on 100 adult non-obese hypothyroid patients. Patients were categorised as per their thyroid profile as: Euthyroidism [(TSH): 0.4-4.0µIU/L with normal FT4], Subclinical hypothyroidism (TSH ≥4.1µIU/L with normal FT4), Overt hypothyroidism (TSH ≥4.1µIU/L and FT4<0.7ng/dL). NAFLD was diagnosed if there was presence of fatty liver by ultrasonography in absence of excess alcohol intake. Results: Prevalence of Overt, Subclinical hypothyroidism and NAFLD were 54%, 46% and 70% respectively. All 'Overt Hypothyroidism' patients had NAFLD. Significantly higher proportion of grade III NAFLD was associated with overt hypothyroidism (92.9%). NAFLD was significantly associated with higher levels of TSH (6.8±1.2µU/L) and lower levels of FT4 (0.6±0.2ng/dl). Conclusion: In present study, subclinical and overt hypothyroidism patients are at a higher risk for development of NAFLD. Increased TSH levels pose a high risk for NAFLD. This study suggests that management of hypothyroidism plays pivotal role in preventing fatty liver disease and its further progression.